2020
DOI: 10.1111/jne.12834
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin receptor signalling modulates novelty recognition but not social preference in zebrafish

Abstract: | INTRODUC TI ONNonapeptides are known to be important players in the regulation of social behaviour across taxa. 1 They evolved from a common ancestral molecule, the arginine vasotocin, after a gene duplication event in early-jawed fish. 2 One copy originated the vasopressin-like peptides, which retained the most primitive functions of the ancestral molecule, namely the regulation of osmotic balance. The other originated the oxytocin (OXT)-like peptides, which have greatly diverged across species, being recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 29 publications
4
42
0
Order By: Relevance
“…Regardless of whether they were raised with mutants or non-mutants, fish that lacked the gene for the oxytocin receptor were always worse at discriminating between a familiar and an unfamiliar fish -a result predicted by previous studies (Ribeiro et al, 2020b). However, other experiments revealed that only mutant fish raised with other mutants were more reluctant to approach other fish and to integrate into a shoal.…”
mentioning
confidence: 64%
“…Regardless of whether they were raised with mutants or non-mutants, fish that lacked the gene for the oxytocin receptor were always worse at discriminating between a familiar and an unfamiliar fish -a result predicted by previous studies (Ribeiro et al, 2020b). However, other experiments revealed that only mutant fish raised with other mutants were more reluctant to approach other fish and to integrate into a shoal.…”
mentioning
confidence: 64%
“…In contrast, when we tested social recognition, which is a form of social memory needed for individuality in social interactions (i.e. differential expression of social behavior depending on identity of interacting individual), that is known to be modulated by oxytocin both in mammals and zebrafish (21,22), we observed that oxtr (-/-) individuals exhibit a deficit in acquisition and retention of social recognition irrespective of the social environment ( oxtr (-/-) or oxtr (+/+) ) in which they were raised (F 1,44 = 7.600, p = 0.008; Figure 1F).…”
Section: Resultsmentioning
confidence: 99%
“…The social preference test assesses the individual’s sociability by observing the interactions between conspecifics (22): a focal fish was placed in a central compartment (30×15×10 cm) of a three-compartment tank, separated by transparent and sealed partitions. A shoal of fish was placed in one of the lateral compartments (15×10×10 cm), while the other contained only water.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exemplarily, Tsuji and colleagues demonstrate that changes in OXT‐ergic signalling components are associated with this behavioural deficiency and identify a critical early postnatal developmental period, in which administration of OXT increases the call rate of valproic acid‐treated pups 9 . Another study by Ribeiro and colleagues uses the zebrafish, an emerging animal model of social behaviour, to demonstrate that OXT signalling differentially regulates social modalities 10 . They find that mutant zebrafish lacking a functional OXT receptor display normal drive to approach conspecifics, whereas their ability to discriminate between novel and familiar fish is impaired.…”
mentioning
confidence: 99%